Plant growth promoting activity of some indigenous Tricho derma isolates and their field performance against sheath blight of rice in old alluvial zone of North Bengal (The Journal of Plant Protection Sciences, 2023)
Five Trichoderma spp. were isolated from the old alluvial zone of North Bengal and their biocontrol activity were  tested in dual culture and found effective against soil-borne plant pathogens, namely, Fusarium oxysporum f. sp.  ciceri (Padw.) Matuo. and Rhizoctonia solani Kühn. Efficacy in plant growth promoting activity of all the isolates  was also tested on cauliflower (Brassica oleracea var botrytis L.), chilli (Capsicum frutescens L.) and tomato  (Lycopersicon esculentum Mill.) with culture filtrate of biocontrol agents and found both positive and negative  effect on seed germination, plant growth and vigour. Maximum increase in germination by 13.64% (chilli), shoot  length by 59.69% (tomato), root length by 84.51% (cauliflower) and biomass by 46.55% (cauliflower) were ob tained by the isolate B16 followed by B14 and B13. However, the isolate, B18 showed negative result with maxi mum reduction in germination by 25.56% (cauliflower), shoot length by 67.06% (cauliflower), root length by  88.50% (cauliflower) and biomass by 34.91% (chilli). Whereas, in the field experiment with talc based bioformula tion (3x108 cfu), all Trichoderma isolates, particularly the isolates, B18 and B16, were found effective to increase  yield (12.50% to 23.14%) and reduce rice sheath blight disease incidence (46.32% to 70.54%) over check plot sig nificantly. Again, the efficacy of the biocontrol agents was significantly greater in the block with green manured  than the block without green manured. Application of hexaconazol 5% EC@ 2.0 ml litre-1and carbendazim 50%  WP @ 1.0 ml litre-1also reduced the sheath blight disease incidence by 53.25% and 56.86% over the check plot  respectively. It was interesting to observe that all biocontrol agents were found effective significantly than the fun gicides. Therefore, the fungal biocontrol agents, particularly, B18 and B16 could be used as biofungicide as well as  biofertilizer for the management of sheath blight of rice.
Keywords: Trichoderma spp; Rhizoctonia solani; sheath blight of rice; plant growth promotion